IMPACT OF PROFESSIONAL SPECIALIZATION AND WORK ENVIRONMENT ON JOB SATISFACTION AMONG PHARMACY TECHNICIANS, FOOD AND NUTRITION SERVICES TECHNICIANS, LAB TECHNICIANS, NURSES, AND X-RAY TECHNICIANS IN SAUDI ARABIA - Thamer Hazzaa Muteb Ibn Busayyis, Atallah Farhan Hamed Alanazi, Naif Matar Alanizy, Manwa Maayof Al Anizy,; Amal Muhammad Abdu Alhafaf, Mushahhin Hamoud Alshammari, Agbal Sayel Al Dhafiry, Musaad Mukalif Alsaadon Alanzi (Chelonian Research Foundation, 2022)
Healthcare technicians play a vital role in the delivery of quality healthcare services. Job satisfaction among these professionals is crucial for ensuring optimal performance and patient care. This study aimed to investigate the impact of professional specialization and work environment on job satisfaction among healthcare technicians in Saudi Arabia. A cross-sectional survey was conducted among 500 healthcare technicians working in various healthcare settings, including primary health care centers, general hospitals, and medical supply departments. Participants included pharmacy technicians, food and nutrition services technicians, lab technicians, nurses, and X-ray technicians. Job satisfaction was measured using the Job Satisfaction Survey (JSS), and data were analyzed using descriptive statistics, one-way ANOVA, and multiple linear regression. The results revealed significant differences in job satisfaction levels across professional specializations and work environments. Pharmacy technicians and nurses reported higher levels of job satisfaction compared to other specializations. Healthcare technicians working in primary health care centers had higher job satisfaction than those in general hospitals and medical supply departments. Multiple linear regression analysis showed that professional specialization and work environment were significant predictors of job satisfaction, after controlling for demographic variables. These findings highlight the importance of considering professional specialization and work environment when developing strategies to enhance job satisfaction among healthcare technicians in Saudi Arabia. Implications for practice and future research are discussed. Keywords: job satisfaction, healthcare technicians, professional specialization, work environment, Saudi Arabia